Adherence to Palivizumab for Respiratory Syncytial Virus Prevention in the Canadian Registry of Palivizumab. Issue 12 (December 2015) - Chan, Parco; Li, Abby; Paes, Bosco; Abraha, Haben; Mitchell, Ian; Lanctôt, Krista L.
Abstract : Background: Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infections in infants. Palivizumab, a means of passive prophylaxis, relies on patient adherence to ensure therapeutic effectiveness. The objective of this study is to evaluate the association between adherence and the incidence of RSV-associated outcomes and to identify demographic factors that may impact adherence. Methods: Infants were recruited into the Canadian registry of palivizumab (CARESS) with parental consent. Monthly interviews collected information on palivizumab administration and RSV-associated outcomes. An infant was considered adherent if they received all of their expected injections or ≥5 injections within the appropriate interdose intervals. Results: Nineteen thousand two hundred thirty-five infants received a total of 83, 447 injections from October 2005 to May 2014. Adherence was more likely in infants with higher maternal education and in those with siblings. Adherence was less likely in infants of aboriginal descent, with mothers who smoke and older infants. Adherence was significantly associated [odds ratio (95% confidence interval), P value] with a lower incidence of RSV infection [0.74 (0.60–0.93), 0.01] but not with RSV-associated hospitalization. However, in those hospitalized for RSV, adherence was significantly associated with the incidence of intubation and duration of hospitalization, intensive care stay and respiratory support. Conclusions: Adherence may have implications in children with less severe RSV infections and those who are already hospitalized for a RSV infection. Our study also identifies subpopulations that are more likely to be nonadherent to palivizumab therapy. Future studies should aim to validate the relationship among adherence, palivizumab levels and RSV-associated outcomes.